2016
DOI: 10.1002/ldr.2499
|View full text |Cite
|
Sign up to set email alerts
|

Surface Runoff Generation and Soil Loss Under Different Soil and Rainfall Properties in The Uluguru Mountains, Tanzania

Abstract: Water erosion is one of the main concerns driving land degradation in mountainous areas throughout the world, and its characteristics change widely with soil and climate conditions in different locations. To investigate the effects of soil and rainfall properties on surface runoff and soil loss, we installed runoff plots (width 0·8 m × slope length 2·4 m) enclosed by corrugated iron sheets, and evaluated water budgets for rainfall, surface runoff and soil moisture for every rainfall event over a rainy season a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 67 publications
(90 reference statements)
3
21
0
1
Order By: Relevance
“…The intensity of rainfall did not differ between the early and late rainy season, and the proportion of strong intensity observed in this study was comparable with the rainfall intensities in other tropical areas with high rainfall intensities (Funakawa et al, ; Nishigaki et al, ).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The intensity of rainfall did not differ between the early and late rainy season, and the proportion of strong intensity observed in this study was comparable with the rainfall intensities in other tropical areas with high rainfall intensities (Funakawa et al, ; Nishigaki et al, ).…”
Section: Discussionsupporting
confidence: 91%
“…These physical properties of Oxisols greatly contributed to the high drainage rate even at wet soil moisture condition and resulted in a low total runoff coefficient in all treatment plots. The runoff coefficient in this study was less than half of that for Alfisols (16·0–16·6%) reported by Nishigaki et al ()), in which the characteristics of surface runoff generation were also evaluated using the same water budget data sets in the Uluguru Mountains in Tanzania. Nishigaki et al () observed that the 0‐ to 30‐cm layer of Alfisols captured rainwater in most of the rainfall events, and the soil moisture content in the 30‐ to 60‐cm layer did not increase as frequently as that of the Oxisol in the present study regardless of the antecedent soil moisture condition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, infiltration may be affected by the drop size distribution (Foley & Silburn, ). Other rain event properties such as event depth or duration may affect infiltration rates through the development of soil hydraulic properties (e.g., Angel, Palecki, & Hollinger, ; Struthers, Sivapalan, & Hinz, ), or through effects on other water balance components including runoff generation (e.g., Nishigaki, Sugihara, Kilasara, & Funakawa, ) and canopy interception (e.g., Zeng, Shuttleworth, & Gash, ).…”
Section: Introductionmentioning
confidence: 99%